2015
DOI: 10.1038/srep08013
|View full text |Cite
|
Sign up to set email alerts
|

Systems approach for the selection of micro-RNAs as therapeutic biomarkers of anti-EGFR monoclonal antibody treatment in colorectal cancer

Abstract: miRNA plays an important role in tumourgenesis by regulating expression of oncogenes and tumour suppressors. Thus affects cell proliferation and differentiation, apoptosis, invasion and angiogenesis. miRNAs are potential biomarkers for diagnosis, prognosis and therapies of different forms of cancer. However, relationship between response of cancer patients towards targeted therapy and the resulting modifications of the miRNA transcriptome in the context of pathway regulation is poorly understood. With ever-inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…In addition, a luciferase reporter assay demonstrated that miR‐545 inhibited the expression of EGFR by blocking its 3′‐UTR activity. Furthermore, the expression of miR‐545 was down‐regulated by the overexpression of HOTAIR but up‐regulated by the inhibition in HOTAIR expression . We also found that the regulatory relationships between HOTAIR and miR‐545, EGFR, and miR‐545 were found to be negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a luciferase reporter assay demonstrated that miR‐545 inhibited the expression of EGFR by blocking its 3′‐UTR activity. Furthermore, the expression of miR‐545 was down‐regulated by the overexpression of HOTAIR but up‐regulated by the inhibition in HOTAIR expression . We also found that the regulatory relationships between HOTAIR and miR‐545, EGFR, and miR‐545 were found to be negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Furthermore, as downstream effectors of EGFR, MAPK, and P38 were shown to be involved in the pathogenesis of CHD. 18,19 Therefore, in this study, we studied the association between the rs4759314 polymorphism and the risk of CHD, and investigated the effect of deregulation of HOTAIR/miR-545/EGFR/MAPK signaling pathway on the pathogenesis of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of evidence indicates that miRNAs are correlated with the drug resistance to anti-EGFR agents. In this context, miRNAs regulate the EGFR signaling; vice versa , EGFR signaling has an impact on the miRNA profiling of cancer cells [ 44 , 46 ]. For example, miR-7 is a tumor suppressor in malignancies including CRC, which is able to target EGFR.…”
Section: Mirnas Regulate Metastatic Colon Cancer By Targeting Signmentioning
confidence: 99%
“…28,29 Using a matched analysis of miR and gene expression from cancer tissue samples, a number of studies have identified cancer subtype-specific miR-regulatory networks that serve as network biomarkers for colorectal and breast cancers. [30][31][32][33] Framework for elucidating MiR-regulatory modules from multi-dimensional omics data. The rapidly increasing availability of transcriptome-wide matched miR and gene expression data via microarray and more recently RNAsequencing technologies has greatly expanded our understanding of miR-gene regulation and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Using a matched analysis of miR and gene expression from cancer tissue samples, a number of studies have identified cancer subtype-specific miR-regulatory networks that serve as network biomarkers for colorectal and breast cancers. 3033…”
Section: Introductionmentioning
confidence: 99%